Thoracic Aortic Aneurysm Development in Patients with Bicuspid Aortic Valve: What Is the Role of Endothelial Cells? - van de Pol, Vera; Kurakula, Kondababu; DeRuiter, Marco C.; Goumans, Marie-José (Frontiers in Physiology, 2017)
Bicuspid aortic valve (BAV) is the most common type of congenital cardiac malformation. Patients with a BAV have a predisposition for the development of thoracic aortic aneurysm (TAA). This pathological aortic dilation may result in aortic rupture, which is fatal in most cases. The abnormal aortic morphology of TAAs results from a complex series of events that alter the cellular structure and extracellular matrix (ECM) composition of the aortic wall. Because the major degeneration is located in the media of the aorta, most studies aim to unravel impaired smooth muscle cell (SMC) function in BAV TAA. However, recent studies suggest that endothelial cells play a key role in both the initiation and progression of TAAs by influencing the medial layer. Aortic endothelial cells are activated in BAV mediated TAAs and have a substantial influence on ECM composition and SMC phenotype, by secreting several key growth factors and matrix modulating enzymes. In recent years there have been significant advances in the genetic and molecular understanding of endothelial cells in BAV associated TAAs. In this review, the involvement of the endothelial cells in BAV TAA pathogenesis is discussed. Endothelial cell functioning in vessel homeostasis, flow response and signalling will be highlighted to give an overview of the importance and the under investigated potential of endothelial cells in BAV-associated TAA.